Recombination mechanisms in crystalline silicon: bulk and surface contributions - Enrichetta Susi (International Journal of Photoenergy)
In the present paper the most interesting results of a work on the influence of some processes used in the fabrication of microstructures on the bulk and surface electrical activity of the Si substrate are reported. In these studies the minority carrier lifetime and the surface recombination velocity were used as sensors of the Si electrical activity changes. Other electrical (DLTS, C-V and I-V characteristics, EBIC) and structural (X-ray double crystal diffractometry, IR spectroscopy) techniques were used to gather information about the nature and concentration of the defects induced by processing.